2022
DOI: 10.1097/bpb.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Cast revision is effective for critical three-point index values in paediatric forearm fractures: a prospective study

Abstract: Three-point index (TPI) has been reported to be effective in predicting the displacement of forearm fractures. The aim of this prospective study was to investigate the clinical efficacy of recasting critical but acceptable casts according to three-point index (0.6 < TPI < 0.8) before a redisplacement occurs in childhood forearm fractures. A TPI of 0.6–0.8 was determined in 68 patients, and these were separated as group 1 (n = 34) applied with prophylactic recasting and group 2 (n = 34) where treatment was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In a very recent study in the literature, it was shown on pediatric forearm shaft fractures that the TPI measured one week after casting had a better predictive value than the first TPI with sensitivity, specificity, positive predictive value, and negative predictive value [19]. As shown in this study, TPI values were found to have changed in our study as well, and it was determined that the renewed TPI measurement after recasting was more valuable.…”
Section: Discussionsupporting
confidence: 69%
“…In a very recent study in the literature, it was shown on pediatric forearm shaft fractures that the TPI measured one week after casting had a better predictive value than the first TPI with sensitivity, specificity, positive predictive value, and negative predictive value [19]. As shown in this study, TPI values were found to have changed in our study as well, and it was determined that the renewed TPI measurement after recasting was more valuable.…”
Section: Discussionsupporting
confidence: 69%